A model proposal to explain the confidence of consumers and entrepreneurs in the Costa Rican economy - Díaz González, José Andrés (2018)
This paper proposes a model to identify how different economic, social and political variables, influence on the confidence that entrepreneurs have towards the Costa Rican economy. The objective of the model is to determine if Costa Rican entrepreneurs behave as rational agents, from a realistic rationality perspective. It is concluded that the confidence of Costa Rican entrepreneurs towards the country’s economy is related to changes in socioeconomic variables, so that these seem to be able to behave as rationalagents.